2012
DOI: 10.1007/s10549-012-2181-7
|View full text |Cite
|
Sign up to set email alerts
|

Low TLR9 expression defines an aggressive subtype of triple-negative breast cancer

Abstract: Toll-like receptor-9 (TLR9) is a DNA receptor widely expressed in cancers. Although synthetic TLR9 ligands induce cancer cell invasion in vitro, the role of TLR9 in cancer pathophysiology is unclear. We discovered that low tumor TLR9 expression is associated with significantly shortened disease-specific survival in patients with triple negative but not with ER+ breast cancers. A likely mechanism of this clinical finding involves differential responses to hypoxia. Our pre-clinical studies indicate that while TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
101
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(118 citation statements)
references
References 41 publications
8
101
1
Order By: Relevance
“…TLR9 overexpression by cancer epithelial [35][36][37][38][39][40][41]. Results from our study are in agreement with those reported in the literature [42].…”
Section: Discussionsupporting
confidence: 92%
“…TLR9 overexpression by cancer epithelial [35][36][37][38][39][40][41]. Results from our study are in agreement with those reported in the literature [42].…”
Section: Discussionsupporting
confidence: 92%
“…4,6 Although initially thought to be limited only to the innate immune system, it is now well established that TLR9 is widely expressed also in various cancer types, such as in breast, brain, gastric, lung, ovarian, prostate and kidney cancers as well as in cancers of the GI tract. [7][8][9][10][11][12][13][14][15][16][17] Stimulation of TLR9 expressing cancer cells with bacterial DNA-like, synthetic TLR9 ligands induces MMP-13-mediated invasion in vitro. 7,10,18,19 Based on these findings, it was expected that tumor TLR9 mediates invasion and metastasis and that high tumor TLR9 expression would be associated with worse survival.…”
mentioning
confidence: 99%
“…In these cancers, low tumor TLR9 expression has been shown to predict poor prognosis and short disease-specific survival. 11,13 Among breast cancer patients, those with TNBC are considered to have the worst prognosis. 21,22 This is because of the generally aggressive behavior of such tumors and also because these tumors lack the expression of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2), which would allow targeted treatment.…”
mentioning
confidence: 99%
“…In addition, it has been previously described that silencing of TLR4 and TLR9 in tumors are associated with mammary tumor progression and decreased activation of IFN-γ-dependent antitumor T-cell responses (49)(50)(51). In this context, our findings reveal an important tumor-promoting function for IL-1R8, a critical break for TLR and ILR stimulus, in breast tumors by supporting cancer associated inflammation and impairing anti-tumor immunity.…”
Section: Il-1r8 Deficiency In a Transgenic Mmtv-neu Mouse Model Attensupporting
confidence: 64%